One way the demand for labor may adapt to the availability of labor - Harriet Orcutt Duleep (Institute for the Study of Labor (IZA), 2012)
This paper presents and tests a model that may partially explain why the demand for labor adapts to the availability of labor. In particular, I postulate that the cost of hiring declines with increases in the amount of labor available. The cost of hiring would decrease with a growth in available labor for two reasons: (1) individuals seeking employment would be coming to employers instead of the latter seeking them out and (2) the larger set of potential employees would increase the probability of employers finding individuals suitable for unfilled jobs. Moreover, individuals seeking employment may engender employers to think of new ways in which labor can be used. An increase in the number of entrants to the labor force would lower the cost of hiring and increase employment demand at any given wage rate. Hence, a change in the labor force - such as the addition of women or immigrants - does not increase unemployment as much as is predicted for current workers because demand for labor increases as the cost of hiring decreases. The paper may provide some insight into the relationship between the size of the labor force and employment demand as recently highlighted by Stock and Watson in their examination of the 2007-2009 recession.
Keywords: J23; J21; J11; J32; 330; labor demand; labor supply; cost of hiring; Arbeitsnachfrage; Arbeitsangebot; Personalbeschaffung; Kosten; Theorie